Ecologia comportamental do tangará Chiroxiphia caudata (aves, Pipridae) no extremo sul da Floresta Atlântica - Della Flora, Franchesco (2010)
The Blue manakin Chiroxiphia caudata is a bird with wide distribution in southern Atlantic forest, ranging from humid forests of the Serra do Mar to the deciduous forests of the Brazilian and Meridional highlands. Although the species is well known for its acrobatic displays, much of their behavior and ecology are unknown or poorly studied. Data about feeding behavior, use of the space and dispersal of seeds, and other results were treated in this dissertation. The study site includes the deciduous forest, far southern Atlantic Forest. Leks of Blue manakin were monitored throughout one year (2006-2007) and data structures of the environment were collected in 2009. These results were divided into four chapters (articles). The first is about the behavioral variation and the use of space throughout the reproductive period and non-reproductive period among three classes of individuals (adult males, young males and females). It is shown that there are differences in behavior patterns and use of space between the sexes and age groups, adult males being more active in the reproductive period and restricted to interior of the leks. Young males tend to live in the edge of territories of adults and they had fewer courtships and vocalizations. Females seem to prefer environments not used by males. The second chapter refers to the diet and seed dispersal. Blue manakin fed on more than 40 plants being that the species with the longest period of fruiting (e.g. Psychotria leiocarpa) or asynchronous (e.g. Ficus) were the most sought after. Besides, there was preference for berries, fruit and small seed sizes, dark-blue coloration, as well as species found in the lower strata of the forest. In relation to seed dispersal, Blue manakin was performed as good seed dispersers; it plays a different type of consumption throughout the year, depositing seeds at specific sites (perches of courtship and call) or random (perches of foraging) in the forest. The third chapter concerns the preference for the dance sites by males. In this study, raises the hypothesis that areas with more density of plants near the perches and attributes of trees that are used by Blue manakin would serve as an indication for adult males choose certain sites instead of others. Variables such as abundance, richness, plant height and number of horizontal branches in the perches of cutting were responsible for the presence of Blue manakin in these courtship sites. This fact would give more care against predators and to the quality of the cooperative and solo displays. The fourth discusses the potential effect of seed dispersal on the perches of courtship. Seedlings under the perches, the use of time by males at these sites and the total fruit consumed showed that C. caudata is effective disperser of species included in its diet. The final chapter chapter focuses on the foraging tactics of Blue manakin uses to capture the fruits of understory plants and test three hypotheses why the species foraging inside and/or outside the plants.